Training for "area" of Rural Education - Wender Faleiro; Geize Kelle Nunes Ribeiro; Magno Nunes Farias (Universidade Federal do Norte do Tocantins, 2020)
The theoretical-reflective study presents considerations on training by area of knowledge in the light of Historical-Critical Pedagogy, dialoguing mainly with Saviani (1999, 2011, 2016), Santos (2013) and Caldart (2011), in order to question why the Degree in Rural Education aims at a training model different from the other degrees implemented in Brazil. Training by area of knowledge will only be constituted if it is within the perspective of interdisciplinarity, in which Field Educators seek to articulate scientific knowledge, overcome its fragmentation and, mainly, have as a reference and give centrality for understanding the reality of the Field and its transformation. It is understood that this type of training is a way to build and produce counter-hegemonic knowledge, as it places the education process in a dynamic and integrated movement between more than one discipline, considering that fragmentation leads to limitation and alienation to understand the realities. Thus, we see the need to move forward in discussions on the structuring aspects of LEdoCs, the purpose and intentionality of the course through the struggle for the education of peasant subjects.